The Correlation between Maternal Exposure to Air Pollution and the Risk of Orofacial Clefts in Infants: a Systematic Review and Meta-Analysis - Ajit Rao; Mairaj K. Ahmed; Peter J. Taub; John S. Mamoun (Stilus Optimus, 2016)
Objectives: The authors performed a systematic review and meta-analysis to investigate the possible correlation between ambient air pollution and orofacial cleft anomalies in newborns. Material and Methods: A literature search was performed using the PubMed and Google Scholar, using the keywords "air pollution", "cleft lip", "cleft palate", "carbon monoxide", "ozone", "sulfur dioxide", "nitrogen oxide", "nitrogen dioxide", and "aerodynamic diameter". Eight epidemiologic articles met the criteria of correlating either carbon monoxide (CO), ozone (O3), nitrogen oxides (NOx), airborne particulate matter of less than 10 µm in diameter (PM10), or sulfur dioxide (SO2) exposures with clefting of the palate alone, clefting of the lip alone, or clefting of the lip and palate. Odds ratios were extracted from the eight studies and tabulated in this meta-analysis. Quality analysis showed six high quality, one medium quality, and one low quality study. Results: Meta-analysis of the combined data confirmed the association of O3 exposure and risk of orofacial cleft anomalies (OR = 1.08; P = 0.02). NOx was consistently associated with decreased risk of cleft lip with or without palate and cleft palate. Conclusions: Ozone showed the strongest correlation with cleft lip and cleft palate anomalies. However, the studies overall showed an inconsistent correlation between orofacial clefts and air pollutants.